Les « choix scolaires » des parents de classe moyenne et supérieure dans leur contexte - Maxime Guinepain (EchoGéo)
Focused on the metropolitan area of Lyon (France), this article relies on a comparison between a social profile analysis of 32 state secondary schools’ recruitment areas and a series of interviews conducted with parents’ representatives. It leads to shed a new light upon the subject of middle- and upper-class “school choice” in urban segregated contexts, showing that even beyond their children’s future, these parents’ own social status is at stake.